HAND HYGIENE INTERVENTIONS AND FOOD SAFETY PRACTICES IN EDUCATIONAL SETTINGS: A SYSTEMATIC REVIEW - Medika Putri Perwita Sari; Victoria Husadani Permata Sari; Anthony Lu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background: Hand hygiene and food safety practices in educational settings remain critical public health concerns, directly impacting student health outcomes and institutional attendance rates. Educational establishments serve as potential transmission sites for respiratory and gastrointestinal infections, making them strategic venues for implementing preventive interventions. Objectives: This systematic review evaluates the effectiveness of hand hygiene and food safety interventions in educational settings on behavioral outcomes and health indicators. Methods: A comprehensive search was conducted across PubMed, Scopus, and Cochrane Library for studies published between 2018 and 2026. Inclusion criteria required interventions targeting hand hygiene or food safety practices in educational settings with quantitative behavioral outcomes. Study quality was assessed using Cochrane Risk of Bias tool version 2 for randomized controlled trials and ROBINS-I for non-randomized studies. Data were synthesized narratively due to heterogeneity in intervention designs and outcome measures. Results: Six studies met inclusion criteria, with sample sizes ranging from 61 to 717 participants across Malaysia, Kenya, Ghana, Saudi Arabia, and Turkey. Among food handlers, handwashing compliance improved from 9.09% to 22.27% (p<0.01), overall food safety compliance increased from 74% to 84% (p<0.001), and contamination prevention scores rose from 62.37 to 90.58 (p<0.001). Among schoolchildren, handwashing after toilet use increased from 0% to 88% (d=2.6, p=0.005), with sustained improvements at follow-up assessments. Conclusion: Educational interventions effectively improve hand hygiene and food safety behaviors in educational settings, particularly when combining theoretical frameworks, demonstrations, and interactive learning components to achieve sustained behavior change.